2019
DOI: 10.1002/chem.201805986
|View full text |Cite
|
Sign up to set email alerts
|

The Hunt for Elusive Molecules: Insights from Joint Theoretical and Experimental Investigations

Abstract: Rotational spectroscopy is an invaluable tool to unambiguously determine the molecular structure of a species, and sometimes even to establish its very existence. This article illustrates how experimental and theoretical state‐of‐the‐art tools can be used in tandem to investigate the rotational structure of molecules, with particular emphasis on those that have long remained elusive. The examples of three emblematic species—gauche‐butadiene, disilicon carbide, and germanium dicarbide—highlight the close, mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…While CCSD­(T) can be considered to be affected by a small N -electron error, the complete basis set (CBS) limit can be accurately estimated by means of extrapolation procedures based on hierarchies of basis sets. , These being computationally demanding already for medium-sized systems, the frozen-core (fc) approximation is usually employed with an additive incorporation of the core–valence (CV) correlation effects. Although CV contributions are usually small for interaction energies of molecules containing only second-row atoms, this is not the case for geometries and, when third-row atoms are present, also for energies …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While CCSD­(T) can be considered to be affected by a small N -electron error, the complete basis set (CBS) limit can be accurately estimated by means of extrapolation procedures based on hierarchies of basis sets. , These being computationally demanding already for medium-sized systems, the frozen-core (fc) approximation is usually employed with an additive incorporation of the core–valence (CV) correlation effects. Although CV contributions are usually small for interaction energies of molecules containing only second-row atoms, this is not the case for geometries and, when third-row atoms are present, also for energies …”
Section: Introductionmentioning
confidence: 96%
“…Although CV contributions are usually small for interaction energies of molecules containing only second-row atoms, this is not the case for geometries and, when third-row atoms are present, also for energies. 12 Focusing on molecular complexes, the accurate description of noncovalent interactions requires the presence of diffuse functions in the basis set (basis sets denoted as "augmented") because these interactions are particularly sensitive to the tails of the wave functions of the partners. In the last decade, a number of systematic investigations have shown that CCSD(T) computations in conjunction with "augmented" triple-and quadruple-ζ basis sets and followed by extrapolation to the CBS limit provide, in most cases, highly accurate results.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In such a situation, an experiment-theory approach is unavoidable, with the support of QC calculations being fundamental for guiding experiments and interpreting the acquired spectra, provided that accurate state-of-the-art methodologies are employed. [7][8][9][10][17][18][19] Concerning the specific topic of this work, creatine phosphate is used to convert adenosine diphosphate to adenosine triphosphate [20] in human skeletal muscle tissue. In a side reaction, creatinine is a breakdown product of creatine phosphate, which is almost exclusively eliminated through the kidney in the urine.…”
Section: Introductionmentioning
confidence: 99%
“…Although CV contributions are usually small for interaction energies of molecules containing only second-row atoms, this is not the case for geometries and, when third-row atoms are present, also for energies. 12 Focusing on molecular complexes, the accurate description of non-covalent interactions requires the presence of diffuse functions in the basis set (basis sets denoted as "augmented") because these interactions are particularly sensitive to the tails of the wave functions of the partners. In the last decade, a number of systematic investigations has shown that CCSD(T) computations in conjunction with "augmented" triple-and quadruple-zeta basis sets and followed by extrapolation to the CBS limit provide, in most cases, highly accurate results.…”
Section: Introductionmentioning
confidence: 99%